2021
DOI: 10.1007/s00167-021-06496-w
|View full text |Cite
|
Sign up to set email alerts
|

Connecting fibers between ATFL’s inferior fascicle and CFL transmit tension between both ligaments

Abstract: PurposeThe lateral ligament complex of the ankle has been extensively studied. Recently an anatomical study described a connection between anterior taloibular ligament inferior fascicle (ATFLif) and calcaneoibular ligament (CFL). The applicability and the mechanical role of these connections have not yet been studied and need to be clariied. The purpose of this study is to evaluate the connection between ATFLif and CFL through a dynamic measurement analysis. Methods An anatomical study was performed in 13 fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…ATFL was known to have bers that merge with CFL extraarticularly [7,8,13,14,22,28], and various types of con uence in the super cial and deep layers had been reported [17]. The ber that connects the ATFL and CFL transmits the tension of both ligaments to each other [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATFL was known to have bers that merge with CFL extraarticularly [7,8,13,14,22,28], and various types of con uence in the super cial and deep layers had been reported [17]. The ber that connects the ATFL and CFL transmits the tension of both ligaments to each other [7].…”
Section: Discussionmentioning
confidence: 99%
“…ATFL was known to have bers that merge with CFL extraarticularly [7,8,13,14,22,28], and various types of con uence in the super cial and deep layers had been reported [17]. The ber that connects the ATFL and CFL transmits the tension of both ligaments to each other [7]. Recently, the LFTCL complex was introduced and described as a complex structure in which the IB of ATFL and CFL merge extraarticularly.…”
Section: Discussionmentioning
confidence: 99%
“…And also, in another study, Hattori S et al [15], found that the distances of the anchor and FOT was 6.0 ± 2.7 mm in open repair and 5.6 ± 3.3 mm in sonographically guided repair, it's very similar to our study, and indicating that the LPF was a very reliable landmarker for suture anchor implantation. Cordier G et al [31], carried out a cadaveric study and found out that the iATFL and CFL was connected by the arciform ber, the this ber was rm enough to transmit the tension between the iATFL and CFL. In fact, in our cadaveric study (not published), the iATFL, CFL and the arciform ber constructed a triangle complex, of which the apexs were located at the anterior border of bular between the bular tip and FOT, the TOT (Talar Obscure Tubercle) and the calcaneus insertion of CFL, so we could augment the iATFL and CFL by one single limb of the suture anchor under arthroscopy (supplementary 1).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with high activity with ATFL and CFL injuries showed higher HU values in the lateral region of the subtalar joint. The inferior fascicle of the ATFL has a fiber connected to the CFL, and these ligaments convey tension to each other and stabilize the subtalar joint as a complex [35]. By combining subtalar instability due to CFL deficiency and high activity, excessive stress to the lateral region of the subtalar joint may be provided.…”
Section: Discussionmentioning
confidence: 99%